EFFECT OF ELECTRICAL CABLE ON MOVEMENT-RANGE OF AGNETIC ACTUATOR SYSTEM CAPABLE OF INSPECTION IN A PIPE - Sasaki , K.; Sato, T.; Yaguchi, H. (Journal of Mechanical Engineering and Sciences, 2014)
This paper proposes a magnetic actuator system of a new type capable of inspection in a complex pipe by means of a new motion principle. Using plural vibration components, the magnetic actuator is able to move in the complex pipe. A magnetic actuator of the reversible type, due to opening and closing of a compound material by using elongation and contraction of four shape-memory-alloy (SMA) coils, was fabricated. In this paper, the influence of the electrical cable length on the moving characteristics of the magnetic actuator is discussed. Twenty electrical cables of 0.12 mm diameter were used in this paper. The experimental result shows that the prototype actuator was able to climb at 15.3 mm/s in the straight pipe when pulling a load mass of 50 g. In addition, the result demonstrated that the magnetic actuator system was able to inspect the complex pipe over a distance of 10 m. This actuator system can inspect a complex pipe with an inside diameter from 40 mm to 50 mm. In addition, the actuator system was able to inspect the pipe with a simple apparatus of three amplifiers and one signal generator.